SAYDAMLIK KURALI BAĞLAMINDA GENEL İŞLEM KOŞULU DENETİMİ YÖNÜNDEN REKABET HUKUKUNDA KOŞUL REKABETİ VE REKABET İHLALİNİN DEĞERLENDİRİLMESİ (II) - (:unkn) unknown (My University, 2019)
0
EVALUATION OF COMPETITION ON TERMS AND COMPETITION VIOLATIONS CAUSED BY THE GENERAL TERMS AND CONDITIONS WITHIN THE CONTEXT OF PRINCIPLE OF TRANSPARENCY IN TERMS OF THE CONTROL OF THE GENERAL TERMS AND CONDITIONS (II)
Keywords: Hukuk